WORLD EXPERIENCE FORMATION OF NATIONAL INNOVATION SYSTEMS: FEATURES OF MODERN TENDENCIES (THE CASE OF THE BRICS) - L. Borisoglebskaya; E. Drozdova (Вестник университета, 2016)
The article shows the features of the modern trends in the formation of national innovation systems on the example of the BRICS countries. The factors are listed and the main approaches for expediting the development of national innovation systems of the BRICS countries.